Identifying New and Structuring Existing Organizational and Technological Approaches to Managing the Cycle of Engineering Preparation for a Construction and Investment Project - Tugaj, O.A.; Shebek, M.O.; Dubynka, O.V. (Science and Innovation, 2024)
Introduction. The development of the construction industry in the country, it is technological and production components require a careful approach to the organizational and management issues of construction and investment projects by building the latest models of interaction of construction participants. Problem Statement. Investment and construction projects occupy almost the entire volume of development real estate, such projects are directly related to both the development of the residential real estate segment and the technological process of construction production, which requires distribution to the organizational and production structure. Purpose. Consideration of the organizational and managerial structure of the construction process at the engineering preparatory stage of the construction and investment project of residential real estate, reflecting the main goals and functions of the project participants. Materials and Methods. Based on a systematic method for studying the design solutions of residential real estate projects using innovative design technologies, engineering, development and implementation of the construction production cycle. Results. An analysis of existing residential development projects and new construction projects suggests that the efficiency of launching construction projects is achieved by timely and coordinated making fundamental decisions at each organizational and managerial level even at the stage of engineering preparation of the construction project. Conclusions. Research and ongoing monitoring of the development of real estate construction based on development indicate the need to determine the optimal model for the effective implementation of investment and construction projects through the use of specific tools for financing, managing, organizing and monitoring the implementation of construction and investment projects. The structure of the selected model requires scientific justification.